LIFE SKILLS ORIENTATION IN MADRASAH CURRICULUM - Ahmadi Ahmadi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
This article intends to elaborate a charge include life skills opportunities in both madrasah curriculum of ibtidaiyah, tsanawiyah and aliyah. The approach used is the science of Islamic education. Some important concepts in Islam that allows it to be analyzed and used as the basis of life skills-based curriculum contained in QS. Al-Ghâsyiyah [88]: 17-20, QS. Fâthir [35]: 39, QS. Al-Jâtsiyah [45]: 12-13, QS. Al-A‟râf [7]: 56-85 and QS. Al-Hujurât [49]: 1, 13, 18. Ethical values (Rasul Muhammad) Islam that allows elaborating life skills is shiddiq, amanah, fathanah and tabligh. The fourth value is assumed to equip graduates of madrassas that he later had a number of personal, social, academic, vocational and soft. The fourth value is assumed to equip graduates of madrassas that he later had the skills. A number of core Islamic values should be in synergy with the age issues such as democracy, globalization, the mastery of science, technology and information (the environment).